Molecular identification of EhCRT gene Calreticulin isolated from children infected with Entamoeba histolytica - Noor Khalf Al-mashhadani; Hatham Ebraheem Khalil; Ahmed Sattar Abood (Journal of the Pakistan Medical Association, 2024)
Objective: To detect the gene of entamoeba histolytica by polymerase chain reaction and investigate the expression of immunogene entamoeba histolytica calreticulin in stool samples of infected patients. Method: The case control study was conducted at Central Teaching Hospital of Paediatrics and Al Mahmoudia General Hospital, Iraq, from December 30, 2020, to September 1, 2021, and comprised diarrhoeal faecal samples collected from 86 children with age ranging from <1 year to 13 years who were suspected of having been infected with entamoeba histolytica. Microscopically positive samples were then subjected to conventional and real-time polymerase chain reaction for the detection of entamoeba histolytica HM1:IMSS strain using Phage shock protein (Psp) gene sequences and detection of entamoeba histolytica calreticulin expression. Result: Of the 86 patients, 71(82.6%) were found to be infected with entamoeba histolytica; 39(54.93%) boys and 32(45.07%) girls. The remaining 15(17.4%) patients were taken as non-amoebic controls; 8(53.3%) boys and 7(46.7%) girls. There were 36(50.70%) cases and 8(53.33%) controls aged 1-4 years. Among the Entamoeba histolytica gene was detected in 44(62%) of the cases using conventional polymerase chain reaction, and immunogene entamoeba histolytica calreticulin was expressed in 36(50.7%) using real-time polymerase chain reaction. Data was analysed using SPSS 24. Conclusion: Polymerase chain reaction was found to be a useful tool for diagnosing entamoeba histolytica infection in children. Key Words: Entamoeba histolytica, Entamoebiasis, Calreticulin, Polymerase, Diarrhea, Bacteriophages